A Comprehensive Review on Data Mining Techniques and Applications - Thakur, A (International Journal of Computer Sciences and Engineering, 2025)
Data mining is the study of mining concealed, helpful patterns and information from data. It is a new technology that helps organizations to estimate future trends and actions, allowing them to make real-world, knowledge driven decisions. The current work discusses the data mining process and how it can help the decision makers to opt for better decisions. Practically, data mining is very productive for large sized organizations with enormous amount of data. It also aids to augment the net profit, as a consequence of right decisions taken during the exact time. This paper presents the different steps taken during the data mining process and how organizations can have better answer to the queries from huge datasets. It also presents a systematic review on data mining techniques and applications.